Implementasi Kewarisan pada Keluarga Penyandang Disabilitas di Desa Karangpatihan (Perspektif Sosiologi Hukum) - Arip Mahendra; Ahmad Junaidi (Journal of Economics, Law, and Humanities, 2022)
In the discussion of inheritance, there are two critical aspects: assets and relatives. So, inheritance must be regulated to realize justice among the heirs. However, the heirs stipulated in the inheritance law guidelines do not always have perfect mental health or are persons with disabilities. Heirs of persons with disabilities cannot carry out legal actions, agreements, or obligations. Being an heir means managing the inheritance to benefit the bereaved family. Thus, the researcher wants to analyze further the implementation of inheritance in the Karangpatihan Village community with a sociological perspective of law, starting from the analysis of the concept of inheritance, the legal basis used, and how somebody can fulfill disability rights. This research is field research with an inductive and qualitative approach. Judging the proposed problem formulation shows that this research is fundamental and empirical. The data was obtained through observation, interviews, documentation, and triangulation. The stages of data processing include the locations of re-examination, data classification, data analysis, and conclusions. The study is reviewed with the theory and indicators of the sociology of law, and findings are obtained from connecting the results of data analysis with the formulation of the problem or anxiety of the researcher. The results showed that the implementation of inheritance in families with disabilities practiced their concept or with the idea of hereditary division, as long as they could maintain harmony, meet daily needs, and not cause conflict. And the protection of inheritance rights in families with disabilities independently does not have the ability, but using collectivity or the use of shared assets, using the concept of cooperation in maintaining inherited assets.